2023
DOI: 10.3390/su15075805
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone-Mediated Mitigation of Negative Effects of Salinity Stress in Solanum lycopersicum through Reducing the Oxidative Damage

Abstract: Soil salinity is one of the main barriers to increasing global food production as it reduces crop growth and productivity. While irrigated lands in arid climates (about 20% of total affected) are more prone to salinization, many other natural and anthropogenic factors contribute to an increase in salinity in arable lands that currently affects over 100 countries and more than one billion ha. Management of agro-ecosystems at every level, including soil, water, and the plant itself, is important in mitigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…GR24 treatment also affects the activity of PIN1, which influences the flow of the plant hormone auxin and is essential for the formation of lateral roots [69]. Furthermore, Fasial et al [23] demonstrated that GR24 can potentially enhance tomato plant growth, including root fresh and dry weights and the root length under salt stress conditions. crop growth and productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GR24 treatment also affects the activity of PIN1, which influences the flow of the plant hormone auxin and is essential for the formation of lateral roots [69]. Furthermore, Fasial et al [23] demonstrated that GR24 can potentially enhance tomato plant growth, including root fresh and dry weights and the root length under salt stress conditions. crop growth and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that using exogenous GR24 in cotton seedlings under salt stress significantly upregulates the genes responsible for antioxidant enzymes, chlorophyll biosynthesis, and the photosynthesis system [22]. Plant growth parameters improved in tomato seedlings treated with GR24 under salt stress, and protein and proline content increased significantly [23].…”
Section: Introductionmentioning
confidence: 92%
“…AnE improved the expression of diverse miRNAs related to nutrient uptake and enhanced salt stress tolerance in A. thaliana [169]. Bioactive organic compounds of AnE have been reported to regulate the union and communication of different transcription factors such as "DREB/CBF, COR47, NF-YA, COR15A, AGF2, CCA1, and LHY1," which improve stress tolerance in plants [170,171]. Rayirath et al [50] observed that AnE application in A. thaliana stimulated the cold-responsive genes "COR15A, RD29A, and CBF3" and improved the plant's cold stress tolerance.…”
Section: Solanum Lycopersicum Tomatomentioning
confidence: 99%
“…Salinity is the most common abiotic stress in arid and semi-arid areas of the world [ 1 ]. Across the globe, 800 million hectares of land are saline [ 2 , 3 ], while in Pakistan, almost 6.8 million hectares are negatively affected by salts [ 4 ]. Salinity adversely affects the morpho-physiological attributes of plants, consequently reducing their yield [ 5 ].…”
Section: Introductionmentioning
confidence: 99%